Toward the deming prize : the case of Tata Steel (A) - Laha, Arnab Kumar; Doutta, Gouttam (London : SAGE Publications Ltd, 2017)
The case series deals with the successful initiation of Tata Steel in various fields. This resulted in Tata Steel becoming lowest cost steel producer in the world. The case series documents the various initiations.
Originally published: Laha, A. & Doutta, G. (2014). Toward the Deming Prize: The Case of Tata Steel (A). PROD0297. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Tata Iron and Steel Company -- History -- Case studies; Steel industry and trade -- India -- Jamshedpur -- Case studies; Iron industry and trade -- India -- Jamshedpur -- Case studies